2011
DOI: 10.1167/iovs.11-8027
|View full text |Cite
|
Sign up to set email alerts
|

Rasch Analysis of the Ocular Surface Disease Index (OSDI)

Abstract: All items demonstrated acceptable fit to the model after collapsing categories to order the response thresholds. The original subscales did not prove valid, and there is some evidence of multidimensionality and poor targeting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
1
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(119 citation statements)
references
References 29 publications
2
115
1
1
Order By: Relevance
“…However, exploratory analyses suggested that dry eye symptoms were associated with visual Dry eye is one of the most common complications reported after LASIK surgery. 7,9,11,[35][36][37][38] Using the OSDI, with its limitations, 39 our findings for dry eye symptoms were incon- All correlations were performed using Spearman rank-order correlation coefficients (satisfaction score vs OSDI Score; all P < .001). Each panel shows analyses with satisfaction scores for 1 of 2 types of satisfaction: satisfaction with vision (A) and satisfaction with surgery (B).…”
Section: Discussionmentioning
confidence: 99%
“…However, exploratory analyses suggested that dry eye symptoms were associated with visual Dry eye is one of the most common complications reported after LASIK surgery. 7,9,11,[35][36][37][38] Using the OSDI, with its limitations, 39 our findings for dry eye symptoms were incon- All correlations were performed using Spearman rank-order correlation coefficients (satisfaction score vs OSDI Score; all P < .001). Each panel shows analyses with satisfaction scores for 1 of 2 types of satisfaction: satisfaction with vision (A) and satisfaction with surgery (B).…”
Section: Discussionmentioning
confidence: 99%
“…9 More detailed examination by an ophthalmologist may be warranted, as traditional tests like Schirmer's dry eye test (which uses paper strips to test for tear production) do not correlate well with symptoms.…”
Section: Brand Namementioning
confidence: 99%
“…All subjects were then asked to complete the Ocular Surface Disease Index (OSDI) questionnaire. 21,22 Clinical measurements were obtained from both eyes. When data were collected from the upper and lower eyelids for a single test, the means of these values were used unless otherwise noted, based on past findings.…”
Section: Study Visitmentioning
confidence: 99%